2023
DOI: 10.1186/s13561-023-00430-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of strategies against coronavirus: a systematic review

Abstract: Background The COVID-19 outbreak was defined as a pandemic on 11 March 2020 by the World Health Organization. After that, COVID-19 has enormously influenced health systems around the world, and it has claimed more than 4.2 million deaths until July 2021. The pandemic has led to global health, social and economic costs. This situation has prompted a crucial search for beneficial interventions and treatments, but little is known about their monetary value. This study is aimed at systematically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…On the other hand, rapid molecular and multiplex tests, which in general are more expensive than RT-qPCR, show promising cost-effectiveness in studies undertaken in emergency rooms and hospital settings in high-resource countries [ 70 , 71 ]. Whatever the option, accurate diagnosis remains critical as effective treatments for COVID-19 have the potential to offer value for money to healthcare systems, people, and society [ 222 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rapid molecular and multiplex tests, which in general are more expensive than RT-qPCR, show promising cost-effectiveness in studies undertaken in emergency rooms and hospital settings in high-resource countries [ 70 , 71 ]. Whatever the option, accurate diagnosis remains critical as effective treatments for COVID-19 have the potential to offer value for money to healthcare systems, people, and society [ 222 ].…”
Section: Discussionmentioning
confidence: 99%
“…We included the ongoing health outcomes and productivity losses associated with severe disease occurring within this one-year time horizon; these ongoing effects were discounted by 3%. The choice to use a time horizon of one year aligned with existing economic modelling for COVID-19, see systematic review [9]. A one-year time horizon was appropriate for the evaluation of oral antivirals since the effects of oral antivirals are short-term and localised to the individual receiving the antivirals.…”
Section: Methodsmentioning
confidence: 99%
“…Research conducted in various settings and countries has consistently demonstrated that widespread mask wearing in public can contribute to reducing the spread of SARS-CoV-2, leading to a decrease in incident cases, hospitalizations, and deaths [8][9][10][11][12][13]. However, despite several economic evaluations of nonpharmaceutical interventions for COVID-19, only a limited number of studies included public mask wearing as a component of their research [14,15]. These studies have primarily examined broader community contexts [16], college campuses [17], or other countries [18][19][20].…”
Section: Introductionmentioning
confidence: 99%